Automatic multi-leaf nonperiodic block-by-block pattern generation and computational analysis of historical masonry structures. (15th May 2023) - Pereira, M.; D'Altri, A.M.; de Miranda, S.; Glisic, B.
Highlights: A block-by-block pattern generator is proposed for multi-leaf nonperiodic masonries. The voxel-based volume of the structure and a pattern sample are used as input. The filling algorithm allows the automatic generation of full-scale patterns. Full-scale patterns are used for block-based simulations of historic structures. The mechanical role of through-thickness blocks is numerically investigated. Abstract: In this paper, an automatic block-by-block pattern generator is proposed for multi-leaf nonperiodic masonries. The outcome is then directly employed in block-based computational analysis of full-scale historical masonry structures. Given the 3D volume of the structure (obtainable also from point clouds) and the 3D block definition of a sample, both in terms of voxels, the volume of the structure is automatically filled with blocks by keeping the blocks statistics of the sample, as well as accounting for through-thickness blocks and structural details, such as lintels and edges. A meaningful benchmark is used to assess the efficiency of the filling algorithm, as well as its capability to generate statistically-consistent patterns. The benchmark is then employed in full-scale computational analyses by using an available block-based model. Various multi-leaf patterns are considered and critically compared in structural analysis, highlighting the influence of through-thickness blocks and intralayer mechanical properties on the overall structural response.